Ciltacabtagene autoleucel: The second anti-BCMA CAR T-cell therapeutic armamentarium of relapsed or refractory multiple myeloma - Chekol Abebe, Endeshaw; Yibeltal Shiferaw, Mestet; Tadele Admasu, Fitalew; Asmamaw Dejenie, Tadesse (Frontiers in Immunology, 2022)
Ciltacabtagene autoleucel (also known as cilta-cel) is a chimeric antigen receptor (CAR) T-cell therapy that targets B-cell maturation antigen (BCMA) on the surface of cancer cells in B cell malignancies, such as multiple myeloma (MM). It is a second-generation CAR that is outfitted with an ectodomain comprising two BCMA-binding single-chain variable fragment (scFv) domains, a transmembrane domain, and an endodomain possessing CD3ζ and 4-1BB. Cilta-cel is an autologous, gene-edited CAR T-cell that is prepared by collecting and modifying the recipient’s T-cells to create a patient personalized treatment in the laboratory to be infused back. This CAR T cell product exceptionally entails CARs with two BCMA-targeting single-domain antibodies that direct two epitopes of BCMA expressed on the malignant cells of MM. Cilta-cel is the current addition to the treatment armamentarium of relapsed or refractory (r/r) MM after its approval by the FDA on February 28, 2022, based on the results of the Phase 1b/2 CARTITUDE-1 study. It was the second approved anti-BCMA CAR T cell product after idecabtagene vicleucel (ide-cel) to treat myeloma patients. It induces early, deep, and long-lasting responses with a tolerable safety profile in r/r MM. Cilta-cel-treated myeloma patients may potentially experience adverse effects ranging from mild to life-threatening, but they are mostly manageable toxicities. Besides, it has a consistent safety profile upon a longer follow-up of patients. Cilta-cel generally outperforms ide cel in terms of efficacy in MM, but shows comparable adverse events. This review highlights the current updates on cilta-cel efficacy, adverse events, comparison with ide-cel, and its future direction in treating MM.